Analyze the Determinants of Capital Structure for Vietnamese Real Estate Listed Companies - Nguyen, Nhung Thi Phuong; Nguyen, Lien Phuong; Dang, Hang Thi Thu (International Journal of Economics and Financial Issues, 2017)
This study adopts a two - step system general method of moments (GMM) approach towards investigating the determinants of capital structure for the listed real estate firms on Ho Chi Minh stock exchange (HSX) in Viet Nam from 2010 to 2015. The determinants of capital structure are mixed and different for short-term and long-term indicators. The real estate firms tend to use more debts to finance their investment. Vietnamese real estate firms should focus on balance structure debt due to complicated impacts of the determinants to their capital structure. There are some implications for the real estate companies and policy of the Government that are based on the empirical results. Keywords: determinants of capital structure, real estate company, general method of moments. JEL Classifications: G32, R3